Memory-enhancing, anxiolytic and antidepressant effects of inhaled Achillea pseudoaleppica essential oil on scopolamine-induced amnesic rats - Akbaba, Emel; Bağcı, Eyüp (My University, 2017)
Achillea pseudoaleppica (Asteraceae) is an endemic plant species of Turkey. Several species of the genus has been used in folk medicine in the treatment of wounds, bleedings, headache, inflammation, pains, spasmodic diseases, flatulence and dyspepsia. In the present study, memory-enhancing, anxiolytic and antidepressant- like activities of A. pseudoaleppica essential oil on scopolamine-induced amnesic rats are assessed. In order to evaluate memory- enhancing activities of A. pseudoaleppica essential oil (1% and 3%, for 21 continuous days) Y-maze and radial arm maze tasks were used. As expected, scopolamine administration decreased spontaneous alternation percentage in Y-maze test and increased the number of working memory errors and the number of reference memory errors in radial arm-maze test. A. pseudoaleppica essential oil used in this study displayed an improved effect on acquisition of the short-term memory of scopolamine-treated rats within the Y-maze task as evidenced by increased spontaneous alternation percentage. A. pseudoaleppica essential oil administered rats also showed significant improvement of reference memory formation, but not working memory formation in radial arm maze test. Furthermore, A. pseudoaleppica essential oil induced anxiolytic effect on elevated plus maze test as evidenced by increased percentage of open arm time, open arm entries and the number of crossings as compared to scopolamine-alone treated rats. A. pseudoaleppica essential oil also exhibited antidepressant-like effects as evidenced by decreased immobility time on forced-swimming test. These results suggest the neuroprotective potential of Achillea pseudoaleppica essential oil on scopolamine-induced amnesia in rats and could act as a promising therapeutic agent for the neurological abnormalities related to Alzheimer's disease.
Bildiri - Yayımlanmış
Keywords: Achillea pseudoaleppica essential oil; Spatial memory; Alzheimer’s disease; Anxiety; Depression